(untitled) - Twyman, Richard M. (New York, 2004)
The Advanced Text series is designed for upper-level undergraduates and graduate students. Titles in this series will also be invaluable to researchers new to a field, and to established researchers as a basic reference text." "Principles of Proteomics is the first textbook designed specifically to explain the different stages of proteomic analysis, their complexities and their jargon to students and researchers interested in a non-technical overview of the field. The author describes the broad range of problems which proteomics can address, including structural proteomics, interaction proteomics, protein modification analysis and functional proteomics. Methodologies are described in user-friendly language, from the more traditional 2-dimensional gel electrophoresis to the new developments in protein chip technologies. These are all presented in the context of overall strategies which can be adopted to address the different aspects of large-scale protein analysis.
Keywords: Proteomics,Nghiên cứu protein